Principles of phylogeography and landscape genetics - Garrick, Ryan (Henry Stewart Talks, 2023)
Principles of phylogeography, Summary statistics to characterize genetic data, Approximate Bayesian Computation (ABC), Comparative phylogeography, Principles of landscape genetics